MINDFULNESS AND SLEEP QUALITY IN STUDENTS OF A PRIVATE UNIVERSITY IN METROPOLITAN LIMA - ROMERO NUÑEZ, LILIANA INES (2024)
THIS STUDY AIMED TO ESTABLISH THE RELATIONSHIP BETWEEN MINDFULNESS AND SLEEP QUALITY IN STUDENTS FROM A PRIVATE UNIVERSITY IN LIMA, PERU. A QUANTITATIVE METHODOLOGICAL APPROACH WAS USED WITH A NON-EXPERIMENTAL DESIGN AND A CORRELATIONAL LEVEL. THE SAMPLE CONSISTED OF 133 STUDENTS FROM SIXTH TO EIGHTH CYCLE OF THE PHYSICAL EDUCATION DEGREE. SLEEP QUALITY WAS ASSESSED USING THE PITTSBURGH SLEEP QUALITY INDEX, AND MINDFULNESS WAS MEASURED WITH THE FIVE FACET MINDFULNESS QUESTIONNAIRE. THE RESULTS REVEALED A NEGATIVE, SIGNIFICANT AND MODERATE CORRELATION BETWEEN SLEEP QUALITY AND MINDFULNESS, SUGGESTING THAT A HIGHER LEVEL OF MINDFULNESS IS ASSOCIATED WITH BETTER SLEEP QUALITY. SPECIFICALLY, THE DIMENSIONS "ACTING WITH AWARENESS", "ABSENCE OF JUDGMENT"AND "DESCRIPTION"WERE FOUND TO SHOW SIGNIFICANT NEGATIVE CORRELATIONS WITH SLEEP QUALITY. THESE FINDINGS INDICATE THAT STUDENTS WITH HIGHER SCORES IN THESE MINDFULNESS DIMENSIONS EXPERIENCE BETTER SLEEP QUALITY. IT IS CONCLUDED THAT PROMOTING MINDFULNESS PRACTICES IN THE UNIVERSITY ENVIRONMENT COULD IMPROVE THE QUALITY OF SLEEP AND THE GENERAL WELL-BEING OF STUDENTS. © 2024 FEDERACIÓN ESPAÑOLA DE ASOCIACIONES DE DOCENTES DE EDUCACIÓN FÍSICA (FEADEF).